Color influence on the use satisfaction of kitchen utensils: An ergonomic and perceptual study - Alves, Ana Laura [UNESP]; de Giuli, Mirela Riquena [UNESP]; Zitkus, Emilene; Paschoarelli, Luis Carlos [UNESP] (Elsevier, 2022)
Different areas of science that study visual perception suggest the influence of color on human behavior and well-being. However, we know very little about the chromatic effect on satisfaction. The study aimed to assess color influence associated with individuals' age on the product's satisfaction of use. A total of 120 female participants (18–29 and 30–55 years old) evaluated a garlic peeler (Experiment I) and a potato masher (Experiment II) in green, red, and gray/silver colors. The methodology used the System Usability Scale Questionnaire, Emotional responses - FaceReader™ software, and a Preference Scale. We noticed no significant difference between age groups regarding the SUS scores in both experiments. However, the gray product received a higher SUS score (p < 0.05) than the other colors, and the Preference Scale rated gray as the worst. On the other hand, in Experiment I, the emotional responses showed that the main variable was the color, and in Experiment II, it was the participants' age (p < 0.05). Based on the present study, we suggest that color is an important variable on the satisfaction of use. The present research presented laboratory experiments that shed light on the importance of color and age variables on the satisfaction of use with kitchen utensils. Relevance to industry: Color and age driven-knowledge can change how professionals and project teams create their products and user interaction, breaking superficial preconceptions. The present study is part of a research project contributing to the Color and Ergonomics in the Design Industrial field.
Keywords: Aesthetics; Color; Ergonomics design; Satisfaction of use; Visual perception